Hepatotoxicity Oral Administration of Flavonoids Rich Extract from Phaleria Macrocarpha in Mice - Siskanita Fitriana; Sri Andarini; Sutrisno Sutrisno; Gita Nawangtantrini; Maharani Maharani (Asian Journal of Health Research, 2023)
Introduction : Herbal medications are increasingly being used to treat a wide range of illnesses. Phaleria macrocarpa, often known as the crown of the gods, is a plant rich in flavonoids that is frequently used in herbal therapy. The goal of this study was to see what effect a flavonoid-rich extract from phaleria macrocarpa has on the livers of mice. Material and Methode : This study used adult female mice aged 6-8 weeks and weighing 20-30 gr as experimental animals, which were divided into four groups: the control group was given distilled water, group 2 was given a flavonoid dose of 500 mg/kg/day, group 3 was given a flavonoid dose of 1000 mg/kg/day, and group 4 was given a flavonoid dose of 2000 mg/kg/day. The flavonoid-rich extract of Phaleria macrocarpa was administered for 28 days. On the 29th day, the mice were necropsied, followed by surgery and examination of the mice's livers. Result : The flavonoid-rich extract of phaleria macrocarpa at a dose of 500 mg/kg body weight/day resulted in no changes in the weight or histological structure of the liver (p>0.05). Hydropic degeneration and necrosis were observed in the group administered the flavonoid-rich extract of phaleria macrocarpa at doses of 1000 and 2000 mg/kg body weight/day. Conclusion : The administration of a flavonoid-rich extract from Phaleria macrocarpa at a level of 500 mg/kg body weight/day caused no harm in the liver of mice. The use of more than 500 mg/kg body weight/day over an extended period of time has hazardous effects and is not recommended.